2014
DOI: 10.3382/ps.2014-03971
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of genistein and hesperidin on immunity and intestinal morphometry in lipopolysacharide-challenged broiler chickens

Abstract: Genistein and hesperidin have been shown to have beneficial effects in several animal models including mice, rats, pigs, and humans. This study investigated the individual and combined effects of genistein (an isoflavone) and hesperidin (a flavanone) on immunity and intestinal morphometry in lipopolysaccharide (LPS)-challenged broiler chickens. Seven hundred twenty 1-d-old commercial Arbor Acres broiler chicks were randomly divided into 6 treatments, with 6 replicates of 20 birds each. Chicks were fed a basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 34 publications
3
51
1
Order By: Relevance
“…Seven (2008) observed that utilization of Turkish propolis (an ISF-enriched source) into the laying hens' diets increased feed intake and improved egg production percentage and FCR values. In contrast, Kamboh and Zhu (2014) reported that genistein and hesperidin did not affect weight gain and FCR in lipopolysaccharide-challenged broiler chicks. These variations in results may be partially explained by the fact that effects of these compounds are dependent on usage dose, duration of use and individual metabolism.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Seven (2008) observed that utilization of Turkish propolis (an ISF-enriched source) into the laying hens' diets increased feed intake and improved egg production percentage and FCR values. In contrast, Kamboh and Zhu (2014) reported that genistein and hesperidin did not affect weight gain and FCR in lipopolysaccharide-challenged broiler chicks. These variations in results may be partially explained by the fact that effects of these compounds are dependent on usage dose, duration of use and individual metabolism.…”
Section: Discussionmentioning
confidence: 86%
“…The lower ADFI in groups fed on the higher dosages of genistein is consistent with findings of Jiang et al (2007), who reported that the levels more than 20 mg soy ISF/kg depress feed consumption in broiler chicks. Of course, some researchers reported that genistein supplementation of broiler chicks had no marked impact on feed intake, weight gain or feed conversion efficiency (Iqbal et al, 2014;Kamboh and Zhu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…But in recent studies, several researchers have reported the gut promotory effects of herbal plants containing adequate amounts of flavonoids in several species of farm animals and poultry; and suggested the antioxidant polyphenols as an important tool to modulate the functional architecture of the small intestine (Awad et al, 2011;Viveros et al, 2011). Some more recent studies have declared that purified flavonoids genistein and hesperidin (Kamboh and Zhu, 2014) and flavonoids-rich fermented Ginkgo biloba leaves (Zhang et al, 2014) could promote the intestinal morphology and absorptive function in growing broilers. Interestingly, while both studies indicated the potential of flavonoids to minimize the deleterious effects of LPS and improved intestinal development in immune-stressed chickens.…”
Section: Gut Modulatory Activity Of Flavonoidsmentioning
confidence: 99%
“…A recent study has demonstrated that citrus and soy flavonoids could significantly improve the immunity of LPS-challenged broilers. The study suggested the use of plant flavonoids as a feed additive to ameliorate the negative effects of circulatory low dose endotoxaemia on animal production (Kamboh and Zhu, 2014). Another study, addressed the IgY enhancing effects of supplemental quercetin in growing broilers, that obviously indicated the potential of quercetin to promote mucosal immunity (Hager-Theodorides et al, 2014).…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%
“…A study by Qiu found that broiler chickens infected with 250 µg/mg LPS showed no significant change in growth performance (Wu, Wang, & Qi, 2016). Additionally, Kamboh and Zhu (2014) demonstrated that repeated intraperitoneal injections of broilers with LPS at a dose of 0.25 mg/kg BW did not affect the performance of the broilers. Zhang, Shi, et al (2017b) found that intraperitoneal infection with a dose of 500 µg LPS per kg BW significantly reduced the value of ADG and ADFI in broilers at 21 days of age.…”
Section: Discussionmentioning
confidence: 99%